2022
DOI: 10.1111/jfpp.17074
|View full text |Cite|
|
Sign up to set email alerts
|

Enhancement of shelf life of moringa bread using Prosopis juliflora extract and gamma radiation

Abstract: With rising health awareness, consumer demand for chemical preservative‐free organic products is also increasing. Incorporation of traditional medicinal herbs and plant sources into daily diet is becoming a trend in society. Hence, the present study aims to formulate baked products like bread using medicinal plant source moringa. Further, the proximate composition and antioxidant activity of the moringa bread (MB) were evaluated along with sensory analysis. For the preservation of MB, it was treated with natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…Studies have found that moringa bread products are more beneficial to human health because they are higher in nutrients and antioxidant activity than regular bread products, which contain less fiber and bioactive substances. 140 Besides, the addition of M. oleifera leaf to biscuits can also increase the iron and protein content of the product, while providing essential amino acids to the human body. 141 It is worth noting also M. oleifera contains large amounts of flavonoids and phenols, which have good antioxidant activity, so it can be used in the development of cosmeceuticals like body washes and lotions, as it is gentle on skin and helps to reduce irritation.…”
Section: Oleifera Used In Health Productsmentioning
confidence: 99%
“…Studies have found that moringa bread products are more beneficial to human health because they are higher in nutrients and antioxidant activity than regular bread products, which contain less fiber and bioactive substances. 140 Besides, the addition of M. oleifera leaf to biscuits can also increase the iron and protein content of the product, while providing essential amino acids to the human body. 141 It is worth noting also M. oleifera contains large amounts of flavonoids and phenols, which have good antioxidant activity, so it can be used in the development of cosmeceuticals like body washes and lotions, as it is gentle on skin and helps to reduce irritation.…”
Section: Oleifera Used In Health Productsmentioning
confidence: 99%